Haemodynamic effects of a prehospital emergency anaesthesia protocol consisting of fentanyl, ketamine and rocuronium in patients with trauma: a retrospective analysis of data from a Helicopter Emergency Medical Service. Issue 12 (20th December 2021) - ter Avest, Ewoud; Ragavan, Dassen; Griggs, Joanne; Dias, Michael; Mitchinson, Sophie A; Lyon, Richard
Abstract : Objectives: Prehospital rapid sequence induction (RSI) of anaesthesia is an intervention with significant associated risk. In this study, we aimed to investigate the haemodynamic response over time of a prehospital RSI protocol of fentanyl, ketamine and rocuronium in a heterogeneous population of trauma patients. Design, setting and participant: We performed a retrospective study of all trauma patients who received a prehospital RSI for trauma by a physician staffed Helicopter Emergency Medical Service in the UK between 1 June 2018 and 1 February 2020. Primary outcome measure: Primary outcome was defined as the incidence of clinically relevant hypotensive (systolic blood pressure (SBP) or mean arterial pressure (MAP) >20% below baseline, with an absolute SBP <90 mm Hg or MAP <65 mm Hg) or hypertensive (SBP or MAP >20% above baseline) episodes in the first 10 minutes post-RSI. Results: In total, 322 patients were included. 204 patients (63%) received a full-dose induction of 3 μg/kg fentanyl, 2 mg/kg ketamine and 1 mg/kg rocuronium, whereas 128 patients (37%) received a reduced-dose induction. Blood pressures decreased on average 12 mm Hg (95% CI 7 to 16) in the full-dose group and 6 mm Hg (95% CI 1 to 11) in the reduced-dose group, p=0.10). A hypotensive episode (mean SBP drop 53 mm Hg) was noted in 29 patients: 17 (8.3%) receiving a full dose and 12 (10.2%) receiving a reduced-dose induction, p=0.69. The blood pressure nadir was recorded on average 6–8 min after RSI. A hypertensive episode was present in 22 patients (6.8%). The highest blood pressures were recorded in the first 3 min after RSI. Conclusion: Prehospital induction of anaesthesia for trauma with fentanyl, ketamine and rocuronium is not related to a significant change in haemodynamics in most patients. However, a (delayed) hypotensive response with a significant drop in SBP should be anticipated in a minority of patients irrespective of the dose regimen chosen.